Crossroad discourses between Christianity and culture - Stoker, W.; Jansen, Henry (Rodopi, 2010)
Christianity exists in relation to and interacts with its cultural environment in a number of ways. In this volume authors from a wide variety of backgrounds explore various facets of the relationship and interaction of Christianity with its cultural environment: politics, society, esthetics, religion and spirituality, and with itself. Divided into three main sections, Crossroad Discourses between Christianity and Culture looks at the interaction of Christianity with culture in the first section, with other religions and spiritualities in the second, and finally with itself in the third. The contributions engage in a critical examinatin of not only the culture in which Christianity finds itself but also in a critical examination of Christianity itself and its interaction with that culture. --